\(\left(x+1\right)\left(x+2\right)< 0\)
Mà x+1 < x+2
\(\Rightarrow\begin{cases}x+1< 0\\x+2>0\end{cases}\)
\(\Rightarrow\begin{cases}x>1\\x< 2\end{cases}\)
\(\Rightarrow x\in\varnothing\)
b)
\(\left(x-2\right)\left(x+\frac{2}{3}\right)>0\)
(+) Với \(\left(x-2\right);\left(x+\frac{2}{3}\right)\) cùng dương
\(\Rightarrow\begin{cases}x+2>0\\x+\frac{2}{3}>0\end{cases}\)
\(\Rightarrow\begin{cases}x>-2\\x>-\frac{2}{3}\end{cases}\)
=> x > - 2
(+) Với \(\left(x-2\right);\left(x+\frac{2}{3}\right)\) cùng âm
\(\Rightarrow\begin{cases}x+2< 0\\x+\frac{2}{3}< 0\end{cases}\)
\(\Rightarrow\begin{cases}x< -2\\x< -\frac{2}{3}\end{cases}\)
=> x < - 2
Vậy x>2 ; x< - 2
a ) \(\left(x+1\right).\left(x-2\right)< 0\)
\(=x.\left(x-2\right)+1.\left(x-2\right)< 0\)
\(=x.\left(x-2\right)+\left(x-2\right)< 0\)
\(\Rightarrow x\in Z\)
\(\Rightarrow x>2\)
b ) \(\left(x-2\right)\left(x+\frac{2}{3}\right)>0\)
\(=x.\left(x+\frac{2}{3}\right)-2.\left(x+\frac{2}{3}\right)\)
\(\Rightarrow\left(x+\frac{2}{3}\right)\in\)số nguyên
Nên \(x\in\) phấn số
a) Vì (x+1)(x-2)<0 nên x+1 và x-2 trái dâu. Mà x+1> x-2 nên x+1>0 => x > -1 ( x thuộc Q)
x-2<0 x < 2
Vậy -1< x < 2 ( x thuộc Q)